Presencia de cadmio (Cd) en la cuenca del río Nanay como indicador de toxicidad en el grano seco de cacao - Iquitos-Loreto. 2022 - Arevalo Vela, Rodolfo Valentino (2022)
The research was carried out in the Nanay River Basin, Maynas, Loreto, to determine the concentration levels of Cadmium (Cd) and its relationship with toxicity in the cocoa crop. It is a quantitative, descriptive, analytical, horizontal and predictive research. The secondary information used from the environmental monitoring of the water was carried out by the National Water Authority (ANA) in the years 2012 - 2021. The study analyzes information from 22 sampling points in different locations for monitoring the parameters of surface water and the variations in the cadmium concentration. A database of time series of cadmium concentrations, their computer processing, analysis, modeling and prediction was built using the Holt-Winters mathematical model. The levels of cadmium concentration in the lakes of the lower and middle basin of the Nanay river: Llanchama, Moronacocha, Rumo cocha and Zungaro cocha show concentration values with an increasing trend in the next monitoring, higher than the LMP of cadmium. For streams such as Allpahuayo and Pucayacu, they report increasing values that do not exceed the LMP, with the exception of the Santo Tomas stream, which reports concentration values above the LMP of 0.00025 mg/L of cadmium in the water. In the rivers of the basin, such as the Chambira and Momón rivers, values with an increasing trend higher than the LMP are reported. While in the Nanay and Pintuyacu rivers they report values with a decreasing trend with values below the LMP for cadmium concentration. It is concluded that the concentration values are very similar with slight fluctuations for the growing and emptying seasons, therefore the null hypothesis is rejected and the alternative hypothesis is accepted, which indicates that the Cadmium concentration levels in the water of the river basin Nanay do not exceed the maximum permissible limits.